The Influence of Transformational Leadership and Islamic Work Ethics on Employee Performance through Organizational Commitment in Islamic Financial Institutions - Salsabilla; Marliyah; Nuri Aslami (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to examine the effects of transformational leadership and Islamic work ethics on employee performance, with organizational commitment serving as a mediating variable in Islamic financial institutions in North Sumatra, Indonesia. A quantitative research approach was employed using a survey method involving 200 employees from various Islamic financial institutions. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to simultaneously examine the relationships among the study variables. The findings reveal that transformational leadership has a positive and significant effect on both employee performance and organizational commitment. Similarly, Islamic work ethics significantly enhance organizational commitment and employee performance, indicating the importance of ethical values in promoting positive workplace outcomes. Furthermore, organizational commitment exerts a positive and significant influence on employee performance and mediates the relationships between transformational leadership and employee performance, as well as between Islamic work ethics and employee performance. These results suggest that the integration of transformational leadership practices with Islamic work ethics fosters stronger organizational commitment, which in turn contributes to higher employee performance. The study provides empirical evidence supporting the strategic role of leadership and ethical values in improving organizational effectiveness within Islamic financial institutions. The findings offer practical implications for managers and policymakers seeking to strengthen employee commitment and optimize organizational performance by cultivating transformational leadership behaviors and reinforcing Islamic ethical principles in the workplace.